Reassessment of the Enteropathogenicity of Mesophilic Aeromonas Species - Teunis, Peter; Figueras, Maria J. (Frontiers in Microbiology, 2016)
Cases of Aeromonas diarrhea have been described all over the world. The genus Aeromonas includes ca. 30 species, of which 10 have been isolated in association with gastroenteritis. The dominating species that account for ca. 96% of the identified strains are Aeromonas caviae, Aeromonas veronii, Aeromonas dhakensis and Aeromonas hydrophila. However, the role of Aeromonas as a true enteropathogen has been questioned on the basis of the lack of outbreaks, the non-fulfilment of Koch’s postulates and the low numbers of acute illnesses in the only existing human challenge study. In the present study we reassess the enteropathogenicity of Aeromonas using dose response models for microbial infection and acute illness. The analysis uses the data from the human challenge study and additional data from selected outbreak investigations where the numbers exposed and the dose were reported, allowing their inclusion as “natural experiments”. In the challenge study several cases of asymptomatic shedding were found (26.3%, 15/57), however, only 3.5% (2/57) of those challenged with Aeromonas developed acute enteric symptoms (i.e. diarrhea). The “natural experiments” showed a much higher risk of illness associated with exposure to Aeromonas, even at moderate to low doses. The median dose required for 1% illness risk, was ~1.4x104 times higher in the challenge study (1.24x104 cfu) compared to natural exposure events (0.9 cfu). The dose response assessment presented in this study shows that the combined challenge and outbreak data are consistent with high infectivity of Aeromonas, and a wide range of susceptibility to acute enteric illness. To illustrate the outcomes, we simulate the risk associated with concentrations of Aeromonas found in different water and food matrices, indicating the disease burden potentially associated with these bacteria. In conclusion this study showed that Aeromonas is highly infectious, and that human susceptibility to illness may be high, similar to undisputed enteropathogens like Campylobacter or Salmonella.